Area-dependent impedance-based voltage shifts during tribocorrosion of Ti-6Al-4V biomaterials: theory and experiment. (24th June 2016) - Gilbert, Jeremy L; Mali, Sachin A; Liu, Yangping
Abstract: Tribocorrosion of medical devices causes the electrode potential across the device-solution interface to become more negative. This study provides a theoretical impedance-based understanding of voltage versus time changes that arise. It combines tribocorrosion with the voltage-dependent impedance characteristics of the surface, the relative anodic and cathodic areas and the mechanics and electrochemistry of oxide abrasion. An area-dependent Randle's circuit is used with the tribocorrosion current equation to show the time-dependent voltage change with disruption and repassivation of the oxide. Heredity integrals are used to predict voltage over time for any arbitrary current-time path. Experiments using titanium pin-on-disk fretting corrosion are used to assess the theoretical model and to demonstrate its behavior.